-4x+9y=-27

Simple and best practice solution for -4x+9y=-27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4x+9y=-27 equation:


Simplifying
-4x + 9y = -27

Solving
-4x + 9y = -27

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9y' to each side of the equation.
-4x + 9y + -9y = -27 + -9y

Combine like terms: 9y + -9y = 0
-4x + 0 = -27 + -9y
-4x = -27 + -9y

Divide each side by '-4'.
x = 6.75 + 2.25y

Simplifying
x = 6.75 + 2.25y

See similar equations:

| -3v+32=-7v+2(1-3v) | | 5x+6y=-18 | | -7x-2y=52 | | 2x^2-2304=0 | | 3+10=80-4 | | 4x+6y=-26 | | (8x+2)-4=18 | | 331x+6=7 | | 13+5= | | 18q=-11 | | q+13=61 | | -5x+49=-8(x-8) | | 8x-110=2x-14 | | 3+2x=x-5 | | 11z^2=-18 | | s+9=37 | | 2+3m= | | b^2-4b-b+4= | | w-8=-2 | | Y=x^2+4x+8 | | 3x*(2x+5)-(x+3)*(3x-1)=1 | | 11z^2+54=36 | | 10x+80=100 | | (3*4)n-9n=39 | | 5.23-(-9.1)= | | X^2=8x-20 | | r^2+4r+6r+24= | | -9.82+(-15.7)= | | m-3=40 | | 12+5=6+23 | | 2x+x+3+x=180 | | X*(x-7)=8 |

Equations solver categories